La constitucionalización del derecho administrativo en colombia. Análisis de la incidencia de la obra del legislador en este proceso - Santaella Quintero, Héctor (Revista de Derecho, 2019)
The constitutional consecration of values, principles and fundamental rights of secondand third generation has given way to a gradual but decided process of transformationof the legal system. Even though traditionally the constitutional justice assumes themain position in this process, the legislative plays also a very important role in itsdevelopment. The analysis of the last reform of the colombian administrative procedureand administrative justice Act shows clearly this situation.
Keywords: Constitutionalization; administrative law; reform; interpretation; administrative procedure; judicial review